A review of line suspended inspection robots for power transmission lines - EKREN, NAZMİ (My University, 2023)
Inspection and maintenance of power transmission lines are crucial in terms of providing uninterrupted power for the consumers. Inspection and maintenance of transmission lines passing through areas that are difficult to reach and pass through are usually carried out by workers or with the help of helicopter. These methods are not effective in terms of time, energy, safety, economy, and efficiency. Transmission line inspection robots can perform this task safely, efficiently, economically, quickly with the least risk. In this study, theoretical and experimental studies on line suspended power transmission line inspection robots in the literature are examined. Details of robots with different mechanisms are presented. Robots, which perform the line inspection process with the help of cameras and sensors, can also overcome various obstacles on the line. Produced robot prototypes have been tested in the field and laboratory environment. In this paper, these robots are grouped as those that move on live lines and ground wires. In addition, the advantages and disadvantages of robots have been determined depending on the line they move. Looking at the studies in the literature, it can be said that the inspection of power transmission lines with the help of robots is the most appropriate method compared to traditional methods.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Fizik Bilimleri; Electrical and Electronic Engineering; Physical Sciences; Inspection robot; Mobile robot; Power transmission line; Review; Robot control; Transmission line inspection